Consciousness and transcendence effects the emotional intelligence and teaching quality among private universities - Saad, Mazni; Azman Ong, Mohd Hanafi; Mohamad Ali, Afiza; Yulinda, Eni (e-International Publishing House, 2024)
The ongoing evolution of high-quality university academics prompts an exploration of the factors defining teaching excellence. This study delves into the impact of consciousness and transcendence, spiritual intelligence (SI) elements, on lecturers' emotional intelligence (EI) and its influence on teaching quality. A structural model was developed utilizing data from a questionnaire survey with 125 usable responses. The results indicate partial mediation by both consciousness and transcendence between EI and teaching quality. This suggests that consciousness and transcendence enhance EI in university teaching, fostering adaptability and inclusivity and promoting transformative learning for well-rounded individuals.